THU0393 INFLAMMATORY BOWEL DISEASES AMONG SECUKINUMAB-TREATED PATIENTS: 24 CASES FROM THE MISSIL REGISTRY. (2nd June 2020) - Letarouilly, J. G.; Pariente, B.; Staumont-Sallé, D.; Goupille, P.; Claudepierre, P.; Varin, S.; Lanot, S.; Dernis, E.; Pascart, T.; Banneville, B.; Baudart, P.; Gombert, B.; et al.
Abstract : Background: An alert regarding about the tolerance of Interleukin 17 (IL-17) inhibitors has been issued from data of randomized controlled trials showing cases of de novo inflammatory bowel diseases (IBD). In a recent analysis of pooled data from 21 clinical trials, cases of IBD events (including Crohn's disease (CD), ulcerative colitis (UC) and inflammatory bowel disease unclassified (IBDU)) were uncommon (1). Yet, real-world data are lacking. Objectives: To describe real-world data about patients treated by IL-17 inhibitors developing new onset IBD (CD or UC). Methods: A French national registry called MISSIL was started in February 2018 to collect the cases of patients treated by IL-17 inhibitors developing new onset IBD. This registry is conducted by rheumatologist, dermatologist and gastroenterologist learned societies specialized on immune-mediated inflammatory diseases. In France, secukinumab (SEK) has been granted market authorization since June 2016 and ixekizumab since April 2018. Results: 24 cases under SEK were reported between February 2018 and January 2020: 3 patients with psoriasis and 21 patients with spondylwoarthritis. There were 20 patients with new onset CD and 4 with UC. Mean age was 51.7 ± 15.7 years old and 12/24 were female; 10 presented an axial spondyloarthritis, 5 a peripheral spondyloarthritis and 6 both, 13/17 were HLA-B27 positive, 7/19 had a radiographic sacroiliitis and 11/17 a MRI sacroiliitis. Only 2 were biological Disease-modifying antirheumatic drug (bDMARD)-naïve. Crohn's disease was mainly located at the ileum, colon and rectum. The median time to onset of symptoms was 2 (1-6) months. The main symptoms were diarrhea, nausea and vomiting and loss of weight. Median CRP at the onset of symptoms was 68 mg/L (41-140.5); 21 patients underwent biopsies, 12 were in favor of CD. IL-17 inhibitors were consistently stopped. Patients were treated by corticosteroids (16/24), mesalazine (7/24), methotrexate (3/24), thiopurines (2/24), infliximab (9/243), adalimumab (3/24), golimumab (2/24), ustekinumab (5/24). The evolution was favorable under treatment with complete resolution (4/24), improvement (11/24) or stabilization (5/24). 3 patients worsened under treatment and 1 died (massive myocardial infarction). Conclusion: IBD flare in patients treated with IL-17 inhibitors are rare and lead to discuss the potential iatrogenic role of IL-17 inhibitor drugs. Further cases are needed to better characterize this complication. A case-control study will be conducted to identify patients at risk to develop IBD under IL-17 inhibitor. References: [1]Reich et al. Incidence rates of inflammatory bowel disease in patients with psoriasis, psoriatic arthritis and ankylosing spondylitis treated with secukinumab: a retrospective analysis of pooled data from 21 clinical trials. Ann Rheum Dis. 2019;78:473-479 Disclosure of Interests: Jean-Guillaume Letarouilly Grant/research support from: Research grant from Pfizer, Benjamin Pariente: None declared, Delphine Staumont-Sallé Speakers bureau: Lilly, Novartis, Philippe Goupille Grant/research support from: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Consultant of: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Speakers bureau: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Pascal Claudepierre Speakers bureau: Janssen, Novartis, Lilly, Stephane Varin: None declared, Sylvain Lanot: None declared, Emmanuelle Dernis Speakers bureau: Lilly, Novartis, Tristan Pascart Speakers bureau: Novartis, Lilly, Beatrice Banneville Speakers bureau: Lilly, Novartis, Pauline Baudart: None declared, Bruno Gombert: None declared, Elodie BAUER: None declared, Laurianne Plastaras: None declared, Sébastien Barbarot: None declared, Renaud FELTEN: None declared, Loïc Le Dantec: None declared, Nathalie Sultan-Bichat: None declared, Céline Girard: None declared, Arnaud Constantin Grant/research support from: Study was sponsored by Sanofi Genzyme, Consultant of: Consulting fees from Abbvie, BMS, Celgene, Gilead, Janssen, Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, Daniel Wendling: None declared, Philippe Gaudin Speakers bureau: Lilly, Denis Jullien Speakers bureau: Lilly, Novartis, Thao Pham Speakers bureau: Novartis, Janssen, Lilly, Rene-Marc Flipo Speakers bureau: Novartis, Janssen, Lilly